The synthesis of novel lanthanum hydroxyborate at extreme conditions - Ibragimova, Olga; Vaquero, Lia; Hussein, Zain; Drozd, Vadym; Chariton, Stella; Prakapenka, Vitali; Chuvashova, Irina (Frontiers in Chemistry, 2023)
The novel structure of lanthanum hydroxyborate La2B2O5(OH)2 was synthesized by the reaction of partially hydrolyzed lanthanum and boron oxide in a diamond anvil cell under high-pressure/hightemperature (HPHT) conditions of 30 GPa and 2400 K. The single-crystal X-ray structure determination of the lanthanum hydroxyborate revealed: 𝑃3 ̅ 𝑐1, a = 6.555(2) Å, c = 17.485(8) Å, Z = 6, R1 = 0.056. The three-dimensional structure consists of discrete planar BO3 groups and three crystallographically different La ions: one is surrounded by 9, one by 10, and one by 12 oxygen anions. The band gap was estimated using ab-initio calculations to be 4.64 eV at ambient pressure and 5.26 eV at 30 GPa. The current work describes the novel HPHT lanthanum hydroxyborate with potential application as a deep-ultraviolet birefringent material.